Protein interactome and cell‐type expression analyses reveal that cytoplasmic FMR1‐interacting protein 1 (CYFIP1), but not CYFIP2, associates with astrocytic focal adhesion. Issue 2 (30th May 2022) - Ma, Ruiying; Pang, Kaifang; Kang, Hyojin; Zhang, Yinhua; Bang, Geul; Park, Sangwoo; Hwang, Eunha; Ryu, Jae Ryun; Kwon, Yujin; Kang, Hyae Rim; Jin, Chunmei; Kim, Yoonhee; et al.
Abstract: The two members of the cytoplasmic FMR1‐interacting protein family, CYFIP1 and CYFIP2, are evolutionarily conserved multifunctional proteins whose defects are associated with distinct types of brain disorders. Even with high sequence homology between CYFIP1 and CYFIP2, several lines of evidence indicate their different functions in the brain; however, the underlying mechanisms remain largely unknown. Here, we performed reciprocal immunoprecipitation experiments using CYFIP1‐2 × Myc and CYFIP2‐3 × Flag knock‐in mice and found that CYFIP1 and CYFIP2 are not significantly co‐immunoprecipitated with each other in the knock‐in brains compared with negative control wild‐type (WT) brains. Moreover, CYFIP1 and CYFIP2 showed different size distributions by size‐exclusion chromatography of WT mouse brains. Specifically, mass spectrometry‐based analysis of CYFIP1‐2 × Myc knock‐in brains identified 131 proteins in the CYFIP1 interactome. Comparison of the CYFIP1 interactome with the previously identified brain region‐ and age‐matched CYFIP2 interactome, consisting of 140 proteins, revealed only eight common proteins. Investigations using single‐cell RNA‐sequencing databases suggested non‐neuronal cell‐ and neuron‐enriched expression of Cyfip1 and Cyfip2, respectively. At the protein level, CYFIP1 was detected in both neurons and astrocytes, while CYFIP2 was detected only in neurons, suggesting the predominant expression of CYFIP1 in astrocytes. Bioinformatic characterization of the CYFIP1 interactome, and co‐expression analysis of Cyfip1 with astrocytic genes, commonly linked CYFIP1 with focal adhesion proteins. Immunocytochemical analysis and proximity ligation assay suggested partial co‐localization of CYFIP1 and focal adhesion proteins in cultured astrocytes. Together, these results suggest a CYFIP1‐specific association with astrocytic focal adhesion, which may contribute to the different brain functions and dysfunctions of CYFIP1 and CYFIP2. Cover Image for this issue: https://doi.org/10.1111/jnc.15410 Abstract : The two members of the cytoplasmic FMR1‐interacting protein (CYFIP) gene family, CYFIP1 and CYFIP2, are associated with numerous brain disorders, including schizophrenia, intellectual disability, and epilepsy. Although several lines of evidence indicate different functions of CYFIP1 and CYFIP2 in the brain, the underlying mechanisms remain largely unknown. Here, we combined protein interactome, cell‐type expression, and gene co‐expression analyses to address this issue. Our approach revealed the predominant expression of CYFIP1, but not CYFIP2, in astrocytes where it associates with some focal adhesion proteins. We suggest that this may contribute to the different brain functions and dysfunctions of CYFIP1 and CYFIP2. Cover Image for this issue: https://doi.org/10.1111/jnc.15410